Comparison of early and intermediate-term outcomes between hybrid arch debranching and total arch replacement: A systematic review and meta-analysis of propensity-matched studies - Naritsaret Kaewboonlert; Worawong Slisatkorn; Apichat Tantraworasin; Punthiti Pleehachinda; Tossapol Prapassaro; Natthipong Pongsuwan; Chanut Chatkaewpaisal; Tummarat Ruangpratyakul (PLoS ONE, 2025)
Objectives To systematically review propensity score-matched studies comparing hybrid arch repair (HAR) with total arch replacement (TAR) for aortic arch pathologies, summarizing early outcomes and intermediate-term results. Methods We searched PubMed, Embase, the Cochrane Library, and Google Scholar to April 2024. The primary outcome was in-hospital mortality, evaluated by a random-effects model to calculate the odds ratio (OR). Time-to-event outcomes were synthesized as hazard ratios (HR) using inverse variance method. Results Eight studies comprising 860 patients were included. There was no significant difference in in-hospital mortality between HAR and TAR groups (OR 0.66; 95% CI 0.33–1.31; p = 0.240). HAR was associated with a lower incidence of renal failure (OR 0.51; 95% CI 0.30–0.88; p = 0.020). In the isolated type A aortic dissection (ITAAD) subgroup, HAR showed a non-significant trend toward lower in-hospital mortality (OR 0.66; 95% CI 0.33–1.31, p = 0.24). In mixed degeneration-dissection (MDAD), TAR showed a non-significant trend toward lower risk of permanent neurological dysfunction (PND) (OR 2.84; 95% CI 0.89–9.10; p = 0.080) and a significantly lower three-year re-interventions rate (HR 2.99; 95% CI 1.48–6.04; p < 0.001). Other postoperative complications did not differ significantly: sternal re-entry for hemorrhage (OR 0.55; 95% CI 0.21–1.43; p = 0.220), and tracheostomy (OR 1.08; 95% CI 0.43–2.72; p = 0.870). Conclusions HAR was associated with a lower risk of renal failure. In ITAAD, HAR showed a trend toward lower in-hospital mortality, whereas in MDAD cohorts, TAR showed a significantly lower three-year re-intervention rate. These findings should be interpreted with caution given the small number of studies and underlying heterogeneity. Further observational studies or randomized trials are warranted.